GRAMMATICAL COHESION IN WRITING RECOUNT TEXT OF THE ELEVENTH GRADE SENIOR HIGH SCHOOL STUDENTS IN SMA NEGERI 1 SENTANI ACADEMIC YEAR 2018/2019 - Putri Rachman (Journal of Education Papua Baru, 2022)
This study was carried out to investigate the realization of grammatical cohesion in writing recount text of the eleventh grade, senior high school students of SMA Negeri 1 Sentani. It aims at finding out the types of cohesion devices frequently used in students’ writing, the most problematic use of cohesion devices, and how cohesive grammar is in students’ writing recount text. The method used in this research was mixed method. The data were analyzed using cohesion category by Halliday and Hassan. The result of this research showed that reference (50.6%) was the most frequently used device in students’ writing amongst cohesion devices. Meanwhile, substitution (0.5) gained the lowest one. Furthermore, the students had adequate knowledge of using more appropriate cohesion devices (528) compared to problematic use of cohesion devices (110). In detail, conjunction (58.49%) became the most problematic use of cohesion devices. However, in average, the students’ writing are  already cohesively satisfied. It can be seen from the average number of cohesiveness percentage that is 81.7%.Keywords: Grammatical Cohesion, Recount Text, Writing ProblemPenelitian ini bertujuan untuk mendeskripsikan penulisan kohesi gramatikal pada teks recount oleh siswa SMAN I Sentani kelas 11. Fokus penelitiannya adalah tipe alat kohesi yang sering digunakan dalam tulisan siswa, alat kohesi yang paling sulit dipakai, dan seberapa kohesif tulisan mereka. Metode penelitian yang digunakan adalah metode campuran. Data dianalisis menggunakan katgori Kohesi oleh Halliday dan Hassan. Hasil menunjukkan bahwa refernsi (50.6%) adalah alat referensi yang paling banyak digunakan. Sementari Substitusi (0.5%) menduduki yang paling jarang digunakan. Selanjutnya, siswa memiliki pengetahuan yang cukup dalam menggunakan alat-alat kohesi (528) dibandingkan yang sulit digunakan (110). Konjungsi (58.49%) adalah yang paling sulit digunakan. Secara keseluruhan, tingkat kohesi tulisan siswa memuaskan dengan rerata presentasi tingkat kohesi 81, 7%.Kata Kunci: Kohesi gramatikal, Teks Recount, Masalah menulis